1988
DOI: 10.1099/0022-1317-69-11-2819
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of Glycoprotein H (gH) in Herpesviruses: Nucleotide Sequence of the gH Gene from Herpesvirus Saimiri

Abstract: SUMMARYWe present the nucleotide sequence of the glycoprotein H (gH) gene of herpesvirus saimiri (HVS), a representative of the T lymphotropic herpesviruses of New World monkeys, and compare the predicted amino acid sequence with sequences of homologous proteins from four human herpesviruses. The HVS gH gene is located within a block of genes encoding products conserved in all herpesvirus subgroups as represented by the human herpesviruses herpes simplex virus, varicella-zoster virus, cytomegalovirus and Epste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 74 publications
1
45
0
Order By: Relevance
“…Generally, gE and gI seem to be important for BoHV-5 neuropathogenicity and its ability to reactivate from latency [53]. Glycoprotein H is one of the most conserved glycoproteins in herpesviruses [46]. BoHV-1 and BoHV-5 gH are both expressed as early-late proteins.…”
Section: Viral Glycoproteinsmentioning
confidence: 99%
“…Generally, gE and gI seem to be important for BoHV-5 neuropathogenicity and its ability to reactivate from latency [53]. Glycoprotein H is one of the most conserved glycoproteins in herpesviruses [46]. BoHV-1 and BoHV-5 gH are both expressed as early-late proteins.…”
Section: Viral Glycoproteinsmentioning
confidence: 99%
“…EHV-4 and HSV-1 gHs and, indeed, throughout the alpha-, beta-and gammaherpesvirus gHs investigated implies some degree of conservation of the secondary and tertiary structure of these proteins presumably involving disulphide bonding (Gompels et al, 1988). The potential of gH to elicit antibody which can neutralize viral infectivity in the absence of complement suggests that the glycoprotein might be a useful constituent of a vaccine preparation.…”
Section: (Iv) Cytoplasmic Domainmentioning
confidence: 99%
“…With the exception of pseudorabies virus gH which is only 686 amino acids in length, the gHs of alphaherpesviruses tend to be larger than their beta-and gammaherpesvirus counterparts, ranging from 838 A comparison of the amino acid sequence of the gH proteins of alpha-, beta-and gammaherpesviruses by Gompels et al (1988) andCranage et al (1988) indicated this greater diversity of sequence in the N-terminal region of the protein and highlighted several features of the gH protein conserved throughout the herpesvirus family: firstly, an unusually short cytoplasmic domain of 14 or 15 amino acids in alphaherpesviruses and of seven or eight amino acids in beta-and gammaherpesviruses, secondly, four conserved cysteine residues at similar positions relative to the putative transmembrane domain and within conserved local sequence, and thirdly, a conserved glycosylation site sequence NGTV 13 to 18 amino acids N-terminal to the transmembrane domain.…”
Section: (Iv) Cytoplasmic Domainmentioning
confidence: 99%
“…Glycoprotein H (gH) of herpes simplex virus type 1 (HSV-1) is one of three glycoproteins that are essential for virus viability in tissue culture (Cai et al, 1988 ;Ligas & Johnson, 1988;Desai et al, 1988), and homologues of this glycoprotein have been identified in members of all the herpesvirus subfamilies (Davison & Taylor, 1987;Gompels et al, 1988;Cranage et al, 1988;Heineman et al, 1988). gH is required for virus entry (Desai et al, 1988) and is probably involved in cell to cell spread of infectivity since gH-specific monoclonal antibodies (MAbs), in addition to neutralizing free virus, inhibit cell fusion by syncytial strains and prevent intercellular virus transmission (Buckmaster et al, 1984;Gompels & Minson, 1986).…”
Section: Induction Of Protective Immunity With Antibody To Herpes Simmentioning
confidence: 99%